The Other Side of the Story: Greenhouse and Nursery Producers’ Perceptions about Neonicotinoid Insecticides and Pollinator Friendly Labeling - Hayk Khachatryan; Xuan Wei; Alicia Rihn (EDIS)
The purpose of this report is to summarize ornamental plant producers’ perceptions about neonicotinoid labeling and anticipated changes in production practices due to neonicotinoids labeling policy intervention. The target audience is industry, state agency, and public stakeholders involved in decisions and policy making related to the use of neonicotinoid insecticides in the U.S. ornamental plants industry.